SEMANTIC AND FUNCTIONAL COMPARISON OF EUPHEMISMS IN UZBEK AND ENGLISH (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article presents a comparative analysis of the semantic and functional aspects of euphemisms in Uzbek and English. The study explores the role of euphemisms in society, their social, cultural, and pragmatic characteristics. The findings indicate that in Uzbek, euphemisms are primarily based on norms of politeness and respect, while in English, they are widely used in formal and diplomatic discourse. Additionally, the research highlights the importance of contextual appropriateness in the translation of euphemisms. This study is of practical significance for the fields of linguistics, translation studies, and cultural studies.